Virtual Lifelines: Filipino Psychologists’ Experiences with Tele-Counseling for Suicide Prevention - Pangngay, Jose J. (Philippine Social Science Journal, 2024)
The COVID-19 pandemic forced a rapid shift to tele-counseling, presenting unique challenges for psychologists, especially those working with high-risk clients. This exploratory multiple-case study investigated the experiences of three Filipino psychologists providing tele-counseling for suicide prevention. The study revealed initial struggles with technology, ethical concerns, and perceived clinical effectiveness. However, the psychologists demonstrated resilience through a two-phase continuous professional development process: orientation and recalibration. Key outcomes included increased clinician enthusiasm, new professional opportunities, and improved ethical responses to crises. Tele-counseling emerged as a client-responsive tool that expands access to mental health services. Despite challenges, tele-counseling can be effective for suicide prevention with proper adaptation and training. These findings underscore the importance of integrating tele-counseling competencies into professional training curricula and developing evidence-based practices for remote crisis intervention.